2007
DOI: 10.1177/0145445507300924
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Parenting Decreases Aggression and Increases Social Behavior in Children With Developmental Disabilities

Abstract: Research shows that after training in the philosophy and practice of mindfulness, parents can mindfully attend to the challenging behaviors of their children with autism. Parents also report an increased satisfaction with their parenting skills and social interactions with their children. These findings were replicated and extended with 4 parents of children who had developmental disabilities, exhibited aggressive behavior, and had limited social skills. After mindfulness training, the parents were able to dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(188 citation statements)
references
References 28 publications
12
169
0
7
Order By: Relevance
“…Both the mindfulness and parent training interventions we are proposing are shorter than the standard interventions delivered (8 and 12 sessions, respectively), as there is growing evidence that these interventions can be less involved (Jensen & Lowry, 2012) even when delivered to parents of children with ID (Dykens et al, 2014). Research suggests that parents of children with developmental disabilities who practice MBSR strategies show improved satisfaction with parenting and satisfaction with the relationships with their children (Singh et al, 2007). Furthermore, for parents who practice mindfulness, meditation gradually becomes a part of their everyday lives (Singh et al, 2010).…”
Section: Intervention Blueprintmentioning
confidence: 99%
“…Both the mindfulness and parent training interventions we are proposing are shorter than the standard interventions delivered (8 and 12 sessions, respectively), as there is growing evidence that these interventions can be less involved (Jensen & Lowry, 2012) even when delivered to parents of children with ID (Dykens et al, 2014). Research suggests that parents of children with developmental disabilities who practice MBSR strategies show improved satisfaction with parenting and satisfaction with the relationships with their children (Singh et al, 2007). Furthermore, for parents who practice mindfulness, meditation gradually becomes a part of their everyday lives (Singh et al, 2010).…”
Section: Intervention Blueprintmentioning
confidence: 99%
“…Previous research has identified mindfulness as an effective intervention for a range of behaviors, including suppression of challenging anti-social behaviors (e.g., Hofmann et al, 2010;Singh et al, 2003;Singh et al, 2007) increases in awareness, and attention to external and internal environmental stimuli (e.g., Wilson & Dixon, 2010). The current study determined the extent to which mindfulness combined with other classroom behavior management strategies would impact student engagement in on-task behavior.…”
Section: Discussionmentioning
confidence: 94%
“…También se ha probado su eficacia en la disminución de los niveles de agresividad en una muestra de estudiantes en riesgo de exclusión social y de adolescentes con Asperger (Singh et al, 2007;Singh et al, 2011). Bögels, Hoogstad, Dun, Schutter y Restifo (2008) encontraron, por otro lado, que la meditación mindfulness ayudaba a mejorar las metas personales, las preocupaciones internas y externas, los problemas de atención, el nivel de felicidad y la conciencia mindfulness en adolescentes con trastornos externalizantes como el déficit atencional, oposicionista-desafiante y del espectro autista.…”
Section: Intervenciones Basadas En Mindfulnessunclassified